Strategy For Strengthening UKM Pempek Palembang Using Local Resources Of Cork Fish During The Covid 19 Pandemic - Nirmala Jayanti; Budi Fachrudin; Yuwinti Nearti (Program Pascasarjana Universitas Sriwijaya, 2023)
The people of Palembang city during the covid-19 pandemic which lasted for approximately 3 years tended to be more selective in buying products, one of which was the most popular Palembang food, namely pempek. The Covid-19 pandemic has also brought significant changes for Small and Medium Enterprises or SMEs in Palembang City. Many SME players have experienced a decline in sales since this pandemic, one of which is the SME Pempek of snakehead fish. Seeing this condition, there is a need for a strategy to strengthen Pempek Gabus Palembang Small and Medium Enterprises during the COVID-19 pandemic using a SWOT analysis. This research was carried out in the city of Palembang by taking samples of the UKM Pempek Ikan Gabus. Research SMEs are Small and Medium Enterprises with 12 respondents whose central location is on Jl. Pakjo Palembang with the consideration that this UKM is one of the producers of cork fish pempek which is still active during the COVID-19 pandemic. Pempek Palembang UKM in order to survive during the COVID-19 pandemic must implement several targeted strategies, including: improving services with 24-hour admin services via wa (chat/phone) so that they can be ordered anytime, the order method made by order, Creating new innovations by using shuji/pandan leaves as a natural dye for pempek and minimizing the fishy smell of fish, making an MoU to snakehead fish farmers so that the availability of raw materials is guaranteed and the price of clothing materials is relatively more stable. In addition, the government, especially the fisheries service, can encourage the community to be more active in cultivating snakehead fish.